A study of the concentrations of lead and cadmium in plants and soil in some farms in Wadi Al-Shati - Edheba Mohammad Shantal; Ibraheem Mohamed Alshareef (Journal of Pure & Applied Sciences, 2022)
This study was conducted in Wadi Al-Shati region in southern Libya to study the concentrations of cadmium and lead in plants and soil in some farms scattered in the region. Plant samples were taken from each farm, which differed from one farm to another. Soil and plant samples were taken from ten randomly selected farms, and plant and soil analyzes were conducted to detect the presence and concentration of the two mentioned metals. The results showed differences in results between different farms. The concentration of lead in the studied soils exceeded the permissible limits in the World Health Organization, where the average of the highest value was 3ppm, and the average of the lowest value was 0.01ppm, and the uncultivated soils of some farms also contained lead. The same applies to cadmium, which concentration in some farms exceeded the internationally permissible limits. The concentration of lead in the studied plants exceeded the permissible limit in the World Health Organization, where the highest value was 8ppm and the lowest value was 1.1ppm, and this confirms the effect of the presence of an accumulation of this element. Cadmium exceeded the permissible limits in plant samples for only two farms, and the plant samples in the rest of the farms were within the permissible limits.